Dynamic electromyographic parameters of masticatory muscles and balance occlusion during partial absence of teeth (Эндодонтия Today)
The study was carried out to study the effectiveness of fixed constructions of dentures, based on the performance of the functional activity of the masticatory muscles and balance the occlusion in patients with partial absence of teeth. The results show that in the 1st group was more rapid and efficient restoration of the balance of occlusion that can be attributed to smaller changes of dental system in the absence of a single tooth.